From mentorship to sponsorship in sport science - Mujika, I.; Leo, P. (International Journal of Sports Physiology and Performance, 2024)
Zur Rolle von Mentoring und Sponsoring für jüngere Wissenschaftler durch erfahrene in der Sportwissenschaft.